PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR SISWA KELAS X MATA PELAJARAN DASAR LISTRIK DAN ELEKTRONIKA PROGRAM KEAHLIAN TEKNIK INSTALASI TENAGA LISTRIK - Sarah Nadiyah Gultom; Abdul Muin Sibuea (JEVTE: Journal of Electrical Vocational Teacher Education, 2022)
Abstract This study aims to determine: (1) student learning outcomes using the Jigsaw Cooperative learning model in basic electrical and electronic subjects at SMK N 1 Percut Sei Tuan; (2) the learning outcomes of students who are taught using the Expository learning model in basic subjects of electricity and electronics at SMK Imelda Medan; (3) the comparison of student learning outcomes who are taught with the jigsaw type cooperative learning model with students who are taught the expository learning model in the basic subjects of electricity and electronics. This research is a research with experimental method using Posttest Design. The research subjects were students of class X Electrical Power Installation Engineering 2 at SMK N 1 Percut Sei Tuan totaling 30 students. There are 28 students in class X Electrical Inslation Engineering 1 at SMK Imelda Medan. The data collected is the posttest value. Analysis of the difference in improvement using the t test. The results of the research show that: (1) the learning outcomes of class X TITL-2 students at SMK N 1 Percut Sei Tuan, the jigsaw type cooperative learning model has an average score of 82.40 with the highest score of 92 and the lowest score of 64. (2) student learning outcomes class X TITL-1 at SMK Imelda Medan with the Expository learning model the average value of 77.57 with the highest score of 88 and the lowest score of 48. (3) the learning outcomes of students who are taught with the jigsaw type cooperative learning model are higher than those taught with the expository model. This is evidenced by the results of the t-test, namely that tcount ttable at a significant level of 0.05 (3.07 1.67). Keywords: jigsaw type cooperative model, expository and learning outcomes. AbstrakPenellitian ini bertujuan untuk mengetahui: (1) hasil belajar siswa dengan menggunakan model pembelajaran Kooperatif tipe Jigsaw pada mata pelajaran dasar lsitrik dan elektronika di SMK N 1 Percut Sei Tuan; (2) hasil belajar siswa yang diajar dengan model pembelajaran Ekspositori pada mata pelajaran dasar listrik dan elektronika di SMK Imelda Medan; (3) perbandingan hasil belajar siswa yang diajar dengan model pembelajaran kooperatif tipe jigsaw dengan siswa yang diajar model pembelajaran Ekspositori pada mata pelajaran dasar listrik dan elektronika. Penelitian ini merupakan penelitian dengan metode eksperimen dengan menggunakan Posttest Design.  Subyek penelitian yaitu siswa kelas X Teknik Instalasi Tenaga Listrik 2 di SMK N 1 Percut Sei tuan berjumlah 30 orang siswa. Siswa kelas X Teknik Inslatasi Tenaga Listrik 1 Di SMK Imelda Medan berjumlah 28 orang siswa.  Data yang kumpulkan adalah nilai posttest. Analisis perbedaan peningkatan menggunakan uji t tes. Hasil peneltian diketahui bahwa: (1) hasil belajar siswa kelas X TITL-2 di SMK N 1 Percut Sei Tuan model pembelajaran kooperatif tipe jigsaw nilai rata-rata 82,40 dengan  nilai tertinggi 92 dan nilai terendah 64. (2) hasil belajar siswa kelas X TITL-1 di SMK Imelda Medan dengan model pembelajaran Ekspositori nilai rata-rata 77,57  dengan nilai tertingii 88 dan nilai terendah 48. (3) hasil belajar siswa yang diajar dengan model pembelajaran kooperatif tipe jigsaw lebih tinggi dari hasil belajar  yang diajar dengan model ekspositori. Hal ini dibuktikan dengan hasil uji t yaitu bahwa thitung ≥ttabel pada taraf siginifikan 0,05 ( 3,07 ≥ 1,67). Kata kunci: model koopeatif tipe jigsaw, ekspositori dan hasil belajar.